(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The current study aims to design, optimize, and assess the niosomal gel containing acyclovir for topical application. Compatibility analysis was carried out to assess potential interactions, using techniques such as FT-IR spectroscopy and DSC thermal analysis. The niosomal suspension was created, optimized, and assessed using a 32 - factorial design. The overlay plot indicates that the F3 formulation was optimized with a 300:20 tween 80 and cholesterol ratio. The improved niosomal solution has been introduced into a gel made of carbopol and thoroughly analyzed for pH, viscosity, spreadability, and in vitro drug release characteristics. The study results demonstrated that the niosomal gel formulation exhibited a sustained release of acyclovir over a 24-hour period. The drug release data was assessed, and the findings unveiled that the medication release from the gel formulation complies with Korsmeyer peppas model. The optimized formulation's stability was demonstrated at various temperatures. The present investigation suggested that the niosome gel formulation (F3) could be a promising vesicular approach for effectively administering acyclovir via topical application.